The impact of teleworking on the Romanians employees' job satisfaction: An empirical evidence based on multiple correspondence analysis (MCA) and logistic regression - Adriana Ana Maria Davidescu; Simona-Andreea Apostu; Vasile Alecsandru; Adrian Istrate Scrădeanu; Ion Daniel Zgură; Maria Gabriela Horga (Amfiteatru Economic Journal, 2021)
The way of working is evolving constantly, and in the last year, the changes have been major under the influence of the COVID-19 pandemic. Even before the pandemic, the work flexibility was encouraged and stimulated in Romania by the promotion of the telework law, becoming an important factor for both employees and employers. In this context, the main goal of this paper is to test if and to what extent teleworking, as an important source of workspace flexibility can impact the way in which Romanian employees self-evaluate their level of satisfaction. In order to reach our goal, the analysis is structured into three main stages. In the first stage an aggregated indicator entitled "employee workspace flexibility composite indicator" is proposed and constructed. This indicator constructed with the help of the MCA technique (multiple correspondence analysis), using the information collected with a national level representative survey for the population of Romanian employees, is further used in logistic models with the purpose of identifying the influence of the flexibility on satisfaction. In the third stage, the main differences between subgroups are identified. The main findings support the idea that flexibility is a significant factor contributing to the increase of satisfaction, and also differences depending on region, sector and form of company.
Keywords: C31; C38; C43; J24; J28; J81; 330; telework; job satisfaction; employee study; composite index; multiple correspondence analysis; logistic regression analysis